STUDY ON THE SIZE STRUCTURE AND POPULATION PARAMETERS OF MUD CRAB SCYLLA SERRATA IN LAWELE BAY, SOUTHEAST SULAWESI, INDONESIA - La Sara (JOURNAL OF COASTAL DEVELOPMENT, 2010)
Population dynamics of mud crab Scylla serrata were studied in Lawele Bay. The objectives were to determine population size structure and population parameters. Samples were obtained monthly using gillnets and baited traps. Less than 70% of gillnet catches during flood tide consisted of adults. Subadults and juveniles were 28.0% and 4.5%, respectively. Similarly, during ebb tide consisted of 51.7%, 24.2% and 24.1%, respectively. It suggests that gillnets are not size selective gear. In contrast, baited traps only caught adults and subadults with percentage of 90.5% and 9.5%, respectively. The CW¥ and K of males were slightly higher than females namely 21.147 and 1.38 for males and 21.023 and 0.83 for females. The mortality estimates are as follows: natural mortality (M) male = 2.48 and fishing mortality (F) male = 1.2, while M female = 1.78 and F female = 0.75. The difference was due to CW¥, K and Z. The results show that S. serrata population is still under exploited.